Optimization of Hot-Electron Bolometers for THz Radiation - Stockhausen, Axel (Karlsruher Schriftenreihe zur Supraleitung / Hrsg. Prof. Dr.-Ing. M. Noe, Prof. Dr. rer. nat. M. Siegel, 2013)
Hot-electron bolometers are fast and low noise radiation detectors which can be used for many different applications. The aim of this work was to optimize the fabrication process of hot-electron bolometers and gain a deeper understanding of the underlying processes. To achieve this, the fabrication of the superconducting thin films was optimized and the superconducting properties of the films were analyzed. Detectors fabricated using the results showed a record value for the noise temperature.